2015
DOI: 10.1080/10508422.2014.948955
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Turkish Version of the Modified Moral Sensitivity Questionnaire for Student Nurses

Abstract: This study examined the validity and reliability of a Turkish version of the Modified Moral Sensitivity Questionnaire for Student Nurses (MMSQSN). After obtaining permission to adapt the MMSQSN into Turkish, the translation/back-translation method was used with expert opinions to determine content validity. Factor analysis was conducted to examine the construct validity and test-retest was performed on the questionnaire to determine reliability. Cronbach's alpha coefficients were calculated to assess for inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
0
13
0
4
Order By: Relevance
“…Nurses who work in this context face peculiar ethical problems that arise from the aspects, issues or ethical implications of everyday life and the production of services. Nurses need to be able to make ethical decisions when faced with ethical problems (2) . Study (3) states that the higher the moral sensitivity of nurses the better is their ethics in clinical decision-making situations.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses who work in this context face peculiar ethical problems that arise from the aspects, issues or ethical implications of everyday life and the production of services. Nurses need to be able to make ethical decisions when faced with ethical problems (2) . Study (3) states that the higher the moral sensitivity of nurses the better is their ethics in clinical decision-making situations.…”
Section: Introductionmentioning
confidence: 99%
“…In that study, however, a simple EFA using Varimax rotation revealed 10 latent components, instead of the six that were theoretically assumed by Lützén and colleagues. A subsequent narrative review of the literature revealed that international scholars building on the work of Lützén and colleagues had also been unable to reproduce the six factors proposed for the original instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Other MSQ studies conducted in many different countries have also evaluated the content and psychometric quality of a 30‐item MSQ. These combinations of items proposed in these studies deviate from the latent constructs proposed by Lützén.…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan uluslararası çalışmaların, hemşirelik lisans programındaki öğrencilerin etik duyarlılık düzeyini belirlemeye yönelik tanımlayıcı araştırmalar olduğu, etik dersi almayan bir kontrol grubu ile karşılaştırma yapılmadığı anlaşılmaktadır. İlk çalışmada, son sınıf hemşirelik öğrencilerinin 5,57 18 Mevcut çalışmadan farklı ve zıt şekilde, Akca ve ark.nın çalışmasında, 20,0±6,7 puan ile "modifiye özerklik" en yüksek, 9,0±5,0 puan ile "kişiler arası oryantasyon" en düşük puan alan alt ölçek olmuştur. 17 Yapılan çalışmalar da, öğrencilerin farklı alt ölçeklerden yüksek ve düşük puanlar aldıkları saptanmıştır.…”
Section: Discussionunclassified
“…15 Ülkemizde hemşirelik öğrencilerinin etik duyarlılık düzeyini değerlendiren az sayıda çalışmaya ulaşılmıştır. Tüm sınıflardan toplam 281 öğrenci ile yapılan bu çalışmada ise ölçek toplam puanına göre hemşirelik öğrencilerinin etik duyarlılığının orta düzeyde olduğu (124,20±31,40), öğrencilerin sınıfları, sosyoekonomik düzeyleri, hemşirelik bölümünden memnuniyetleri, etik dersi alma ve etikle ilgili yayın takip etme durumları, etik ikilem yaşama durumları ile etik duyarlılık düzeyleri ara- 18 Bu çalışmada ise Cronbach alfa değeri 0,74 olarak bulunmuştur.…”
unclassified